Generación de conocimiento en las organizaciones apoyada por la Teoría General de Sistemas (Knowledge creation in the organizations aided by the General Systems Theory) - Martínez, J.M. (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. This article pretends to make a linkage between the General Systems Theory and organizational knowledge generation, exposing the advantages of the use of this theory. Researches were used in order to let the reader to form his/her own criteria according the environment that is involved. Isolating the facts, not considering the organization to the decision making process will limit the development of the organizational knowledge, because al last, this knowledge will be losing when the individual are retiring from the organization. What is proposing is that the knowledge remains through a proper application of generation and retaining with constant renovation methods.